Decision Support System for Selection of Thesis Advisors Supervisors Thesis Advisors according to the Field of Science Using the AHP Method - Jelita Sari Simanungkalit; Hengki Tamando Sihotang (Institute of Computer Science (IOCS), 2020)
Thesis is a scientific work and a condition that must be taken in order to achieve a bachelor's degree. Thesis supervisors play an important role because they have the responsibility and ensure that students are able to compile the thesis properly so that it is ready for testing and quality. In higher education, a system is needed that can help and ease a job, especially in the selection of thesis supervisors. In selecting the thesis supervisor, it is still based on subjectivity, which causes the title submitted by students to not match the field of science of the thesis supervisor so that the lecturer appointed to guide the topic of the title submitted by students has a different field of expertise from the student's title. In this determination, there are sometimes less than optimal decisions where the appointed lecturer is not in accordance with the thesis topic proposed by the student. This system is made using the AHP method so that the programmed system can be carried out more effectively. AHP method is one of the methods used in decision support systems with the calculation process by comparing each criterion.